Quantitative EEG parameters can improve the predictive value of the non-traumatic neurological ICU patient prognosis through the machine learning method - Tian, Jia; Zhou, Yi; Liu, Hu; Qu, Zhenzhen; Zhang, Limiao; Liu, Lidou (Frontiers in Neurology, 2022)
Background: Better outcome prediction could assist in reliable classification of the illnesses in neurological intensive care unit (ICU) severity to support clinical decision-making. We developed a multifactorial model including quantitative electroencephalography (QEEG) parameters for outcome prediction of patients in neurological ICU. Methods: We retrospectively analyzed neurological ICU patients from November 2018 to November 2021. We used 3-months mortality as the outcome. Prediction models were created using a Linear Discriminant Analysis (LDA) based on QEEG parameters, APACHEII score, and clinically relevant features. And we compared our best models with APACHEII score and Glasgow Coma Scale (GCS). Delong test was carried out to compare the ROC curves in different models. Results: 110 patients were included and divided into a training set (n=80) and a validation set (n=30). The best performing model had an AUC of 0.85 in the training set and an AUC of 0.82 in the validation set，which were better than that of GCS(training set 0.64, validation set 0.61). Models in which we selected only the 4 best QEEG parameters had an AUC of 0.77 in the training set and an AUC of 0.71 in the validation set，which were similar to that of APACHEII (training set 0.75, validation set 0.73). The models also identified the relative importance of each feature. Conclusion: Multifactorial machine learning models using QEEG parameters, clinical data, and APACHEII score have a better potential to predict 3-month mortality in non-traumatic patients in neurological ICU.